U.S. Healthcare : A Story of Rising Market Power, Barriers to Entry, and Supply Constraints - Lin, Li (IMF Working Papers; Working Paper ;, 2021)
Healthcare in the United States is the most expensive in the world, with real per capita spending growth averaging 4 percent since 1980. This paper examines the role of market power of U.S. healthcare providers and pharmaceutical companies. It finds that markups (the ability to charge prices above marginal costs) for publicly listed firms in the U.S. healthcare sector have almost doubled since the early 1980s and that they explain up to a quarter of average annual real per capita healthcare spending growth. The paper also finds evidence that the Affordable Care Act and Medicaid expansion were successful in raising coverage and expanding care, but may have had the undesirable side-effect of leading to labor cost increases: Hourly wages for healthcare practitioners are estimated to have increased by 2 to 3 percent more in Medicaid expansion states over a five-year period, which could be an indication that the supply of medical services is relatively inelastic, even over a long time horizon, to the boost to demand created by the Medicaid expansion. These findings suggest that promoting more competition in healthcare markets and reducing barriers to entry can help contain healthcare costs.